Rising Incidence and Comorbidities of Endogenous Hypothyroidism in Republic of Korea from 2004 to 2018: A Nationwide Population Study - Chae Won Chung; Hwa Young Ahn; Sun Wook Cho; Ka Hee Yi (Endocrinology and Metabolism)
Background Hypothyroidism, a prevalent endocrine disorder, results from insufficient thyroid hormone production or release, affecting metabolism. However, disparities in comorbidities and treatment trajectories may exist between endogenous and exogenous hypothyroidism. Methods Data from the Korean National Health Insurance Service from 2004 to 2018. Endogenous hypothyroidism was defined as cases with two or more diagnostic codes for hypothyroidism coupled with a history of thyroid hormone intake exceeding 60 days. To eliminate iatrogenic hypothyroidism, individuals with diagnosis codes for thyroid cancer, treatment codes for thyroid surgery, or radiotherapy were excluded. Hypothyroidism-related comorbidities were defined as new occurrences of the corresponding diagnosis code after the diagnosis of hypothyroidism during the entire study period. Results The age-standardized incidence of endogenous hypothyroidism among men was 0.2 per 1,000 person-years in 2004, increasing to 0.8 in 2018. Among women, the incidence increased from 1.6 per 1,000 person-years in 2004 to 3.7 in 2018. When comparing age groups of 20s–50s and 60s–90s, both sexes in the 60s–90s demonstrated a more rapid increase in incidence than those in the 20s–50s age range. Patients with endogenous hypothyroidism demonstrated a higher incidence of mood disorders across all age groups and cerebrovascular disease in individuals ≥60 years old, regardless of sex. Conclusion In Republic of Korea, endogenous hypothyroidism incidence has been increased in recent years. The incidence of endogenous hypothyroidism is increasing more rapidly in men than in women, especially in the elderly. Patients with endogenous hypothyroidism seem to have a heightened risk for cerebrovascular disease and mood disorders.